Evaluation of Safe Kids Week 2001: prevention of scald and burn injuries in young children. Issue 2 (1st June 2003) - Macarthur, C
Abstract : Objective: To evaluate Safe Kids Week 2001—a national public awareness campaign on scald and burn prevention—run by Safe Kids Canada. Design: Random digit dial telephone survey. Setting: Canada. Subjects: Parents or guardians of children under 9 years. Two groups of parents were compared, those "exposed" to the campaign (defined as having "seen, heard, or read anything about scald and burn prevention during the period 28 May to 3 June 2001") and those "unexposed" to the campaign. Intervention: Burn safety information was disseminated via the media, 5000 retail stores, and 348 community partners across Canada. The campaign emphasized four key messages: (1) Lower your water temperature, hot tap water could burn your child! (2) Make sure your child is safe in the kitchen. (3) Keep hot drinks away from your child. (4) Check your smoke alarms regularly. Outcome measures: Change in parental knowledge and behavior. Results: A total of 29 871 telephone numbers were called, with a household refusal rate of 27%. Nationally, 14% of parents were exposed to the campaign and 504 parents were interviewed, 251 in the "exposed" group and 253 in the "unexposed" group. Parents exposed to Safe Kids Week 2001 were 1.5–5 times more likely to be aware of key campaign messages, and 2–3 times more likely to test and lower the water heater temperature, compared with unexposed parents. Conclusion: Safe Kids Week 2001 reached a significant proportion of parents of young children. In addition, the campaign appeared to increase burn safety knowledge and lead to behavior changes among exposed parents, compared with unexposed parents.